Growth of Freshwater Microalga, Botryococcus sp. in Heavy Metal Contaminated Industrial Wastewater - Onalo, Joan Iye; Peralta, Hazel Monica Matias; Mohamed Sunar, Norshuhaila (Journal of Science and Technology, 2014)
The aim of this study was to determine the growth and the bioremoval capacity of the green microalga, Botryococcus sp. grown in industrial wastewater contaminated with heavy metals. The freshwater green microalga, Botryococcus sp. was cultured in different concentrations of wastewater (25%, 50% and 100%) with an initial cell concentration of 1000 cells/ml for a period of 12 days. Bold basal medium and sterile distilled water were used as positive and negative control, respectively. The Botryococcus sp. grown in Bold’s basal medium showed the highest (P